Navigating amidst complexity: guide to implementing effective research and development to improve livelihoods and the environment - Campbell, Bruce M.; Hagmann, J.; Stroud, Ann; Thomas, R.; Wollenberg, Eva Karoline (Center for International Forestry Research, 2006)
This booklet is directed towards those who are implementing natural resource management (NRM) projects, undertaking research on NRM, or setting policies for NRM. It is focused on the best ways to improve the effectiveness of research and development (R&D) in NRM, so that livelihood and environmental outcomes are enhanced. What is described here can be thought of as a “new way of doing business” for R&D in natural resource management, but builds on approaches in the agricultural, conservation and governance fields. Section 1 explains why we need to increase the effectiveness of R&D. The section indicates how a more integrated approach has evolved and illustrates how it can be applied (Section 1.4). For the sceptics of holism and integration, we clarify that achieving holism is often impossible and can be counter-productive (Section 1.5). Section 2 briefly describes the foundations of the approach. Section 3 of the publication covers the operational cornerstones for effective R&D interventions. Section 4 discusses the management of research for development processes. Section 5 concludes. The foundations and cornerstones presented in this booklet were established during a series of four workshops involving over 200 scientists from the Consultative Group on International Agricultural Research (CGIAR) and its partners. Specialists were drawn from the full spectrum of land use systems and NRM perspectives: conservation, forestry, fisheries, irrigated agriculture, dryland agriculture, and livestock production – covering the humid to arid tropics.